Diseño y estructuración de un modelo de gestión de recursos humanos para vendedores a partir de competencias. Caso aplicado en la empresa Excellent Service SICOR. - Lema Lliguicota, Luis Fernando (2010)
The aim of my thesis is the creation and implementation of a system of adequate skills to our reality, we give a method to support consumer companies with vendors; which consists of a system applicable thanks to the retro power that gives us the selection, recruitment and evaluation updated.